2016
DOI: 10.1007/s00248-016-0814-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and Antibiotic Resistance Genes in Sediment of Honghu Lake and East Dongting Lake, China

Abstract: Sediment is an ideal medium for the aggregation and dissemination of antibiotics and antibiotic resistance genes (ARGs). The levels of antibiotics and ARGs in Honghu Lake and East Dongting Lake of central China were investigated in this study. The concentrations of eight antibiotics (four sulfonamides and four tetracyclines) in Honghu Lake were in the range 90.00-437.43 μg kg (dry weight (dw)) with mean value of 278.21 μg kg dw, which was significantly higher than those in East Dongting Lake (60.02-321.04 μg k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…A similar phenomenon was also found in the Baiyangdian Lake [61]. However, this finding is inconsistent with previous studies in the Yangtze Estuary [39], South Yellow Sea [29], Honghu Lake and East Dongting Lake [62].…”
Section: Relationships Between Basic Parameters and Antibiotic Concencontrasting
confidence: 64%
“…A similar phenomenon was also found in the Baiyangdian Lake [61]. However, this finding is inconsistent with previous studies in the Yangtze Estuary [39], South Yellow Sea [29], Honghu Lake and East Dongting Lake [62].…”
Section: Relationships Between Basic Parameters and Antibiotic Concencontrasting
confidence: 64%
“…A total of 14 out of 23 target antibiotics were found in sediments at Ningbo city with concentrations ranging from not detected or < LOQ (limit of quantification) to 4496.0 ng/g (Fig. ), magnitudes similar to those commonly found in Chinese freshwater and marine sediments (Liu et al, ; Yang et al, ). The residual patterns of the antibiotics were generally related to medicine prescription and environmental stability.…”
Section: Resultssupporting
confidence: 57%
“…Honghu Lake, which is located in central China, suffers from high-intensity human activities and lack of adequate sewage treatment facilities (wastewater treatment rate at only 38%) (Yang et al, 2016). For example, the densities of population, livestock, and poultry in Honghu Lake watershed are approximately 570 individuals, 800 pigs, and 14,000 poultry per square kilometers (JBS, 2016); moreover, over 40% of the total area of Honghu Lake is used as aquafarms for high-density culturing of fish, crabs, crawfish, and shellfish, with annual products of approximately 0.3 million tons Yang et al, 2016).…”
Section: Occurrence and Concentrations Of Antibioticsmentioning
confidence: 99%
“…These results indicated that the aquaculture application and the point or non-point discharge are mainly responsible for the occurrence of antibiotics in the Honghu Lake region. This phenomenon is mainly caused by the high-intensity and large-area aquaculture in Honghu Lake (fishery enclosure in Honghu Lake was over 40% of the total area of the lake) and lack of the wastewater treatment facilities in this region (Yang et al, 2016).…”
Section: Correlation Between Antibiotics and Environmental Parametersmentioning
confidence: 99%